WAYS TO ORGANIZE EXTRACURRICULAR ACTIVITIES TO DEVELOP QUICK ENGLISH LEARNING SKILLS IN PRIMARY SCHOOL STUDENTS: WAYS TO ORGANIZE EXTRACURRICULAR ACTIVITIES TO DEVELOP QUICK ENGLISH LEARNING SKILLS IN PRIMARY SCHOOL STUDENTS - Saparbaeva, Suliwxan (Журнал иностранных языков и лингвистики, 2025)
English has solidified its position as the global lingua franca, playing a pivotal role in international business, science, technology, and education. Recognizing its significance, many countries are integrating English language instruction early in the educational journey. For instance, Algeria has expanded English education in elementary schools, introducing two 45-minute English lessons weekly for third and fourth graders, aiming to align with global standards and reduce the dominance of French in its educational system.